Nutrition planning for lots of laying hens, using fuzzy linear optimization techniques - Morán Carril, Augusto (2020)
In this work the fuzzy formulation of the diet problem in the planning of the nutrition of the farms of laying hens is done, and then it is solved applying the methods proposed by Lai and Hwang and by Zimmermann.Finally, we solve a nutritional planning problem with twelve products of which 4 are diffuse and with 10 nutritional substances.